PENGEMBANGAN MEDIA AUDIOVISUAL BERBENTUK ANIMASI UNTUK MENINGKATKAN KETERAMPILAN MENGANALISIS INFORMASI SISWA KELAS V SD TUNAS PELITA BINJAI - Ajeng Sestya Ningrum; Wisman Hadi; Daulat Saragih (JURNAL TARBIYAH, 2022)
The purpose of this research is to develop audiovisual tools in the form of animation to improve the skills to analyze information of students Category V SD Tunas Pelita Binjai. This research is motivated by the lack of audiovisual media applications in elementary schools and teachers less improve audiovisual media. The formulation of the problem in this research is: a) How to develop audiovisual Media in the form of animation on the“ theme of 7 events in life and subtheme (2) national events of the colonialism Era?”. b) How is the feasibility of audiovisual Media in the form of animation to improve students ' information analysis skills on“ theme 7 events in life and subtheme (2) national events of the colonialism Era?”. c) How is the effectiveness of audiovisual media in improving students ' information analysis skills on“ theme 7 events in life and subtheme (2) national events of the colonialism Era”. This research was conducted in SD Tunas Pelita Binjai with the number of participants is 30 students of fifth grade. The procedure for this research is development (research and development). The results of this research is to show that the way the development of audiovisual Media in the form of animation on the " theme of 7 events in life and subthemes (2) get the submission in the category of good and right. The feasibility of audiovisual media obtained with valid type where the evaluation of experts tried totality, this animated video product obtained 227 numbers with a percentage of 87, 31%( valid type). Expert evaluation to the large group trial if the animated video products in this research get the number 243 with a percentage of 93. 46% (type of breast milk). Furthermore, for the use of audiovisual tools obtained thcount= 8, 82 from the listxtribution t by usingopportunities 1- α =0, 95 with cdk n - 1 (6 - 1)= 5 obtained price ttable= 2, 07. The result is obtained t Number T table, that is.